Maths for real. (2nd April 2021) - Watson, Nicola
Abstract : Changes to the Maths Early Learning Goals place an emphasis on supporting children to gain a depth of knowledge and a secure understanding of numbers to ten. Space, shape and measure now form part of a holistic approach to the subject rather than representing a separate goal, says Nicola Watson.